Multimodal optical coherence tomography, Raman spectroscopy and IR fundus imaging for in vivo retinal imaging - Sentosa, Ryan; Stiebing, Clara; Eibel, Matthias; Salas, Matthias; Jong, Wim De; Jolan-Jahn, Izabella; Schmitt, Michael; Krestnikov, Igor; Ensher, Jason; Baumann, Bernhard; Pollreisz, Andreas; Garhöfer, Gerhard; et al. (Optics InfoBase Conference Papers, 2022)
Combined optical coherence tomography (OCT), OCT angiography, Raman spectroscopy and infrared tracking in an ophthalmic device to investigate human retinal tissue in a clinical setting is presented.
CRIS-Team Scopus Importer:2023-04-20